Persistent damage to Enterocytozoon bieneusi, with persistent symptomatic relief, after combined furazolidone and albendazole in AIDS patients. Issue 10 (October 1998) - Dionisio, D; Manneschi, L I; Di Lollo, S; Orsi, A; Sterrantino, G; Leoncini, F; Pozzi, M; Vinattieri, M A; Tani, A; Papucci, A
Abstract : AIM: To investigate morphological changes in Enterocytozoon bieneusi and the duration of symptomatic relief after combination treatment with furazolidone and albendazole in AIDS patients. METHODS: Four severely immunocompromised AIDS patients with symptomatic E bieneusi infection of the gut received an 18 day course of combined furazolidone and albendazole (500 + 800 mg daily). All patients were monitored for parasite shedding in stool by light microscopy at the end of treatment and monthly during follow up. At the end of treatment, duodenal biopsy specimens obtained from three patients were studied by transmission electron microscopy by two pathologists blind to the patients' treatment or clinical outcome. Duodenal biopsy specimens obtained from one of the patients two months after completion of treatment were also studied electronmicroscopically. RESULTS: All patients had long lasting symptomatic relief, with a major decrease–or transient absence–of spore shedding in stools from completion of treatment. After treatment, changes in faecal spores were persistently found by light microscopy in all cases, and there was evidence of both a substantial decrease in the parasite load and ultrastructural damage in the parasite in all biopsy specimens. The treatment was well tolerated, and no patient had clinical or parasitological relapse during follow up (up to 15 months). CONCLUSIONS: The long lasting symptomatic relief observed in all four treated patients correlated with the persistent decrease in parasite load both in tissue and in stool, and with the morphological changes observed in the life cycle of the protozoan. These data suggest that combined treatment with furazolidone and albendazole is active against E bieneusi and may result in lasting remission even in severely immunocompromised patients.